Reconstruction of Natural Slope Stability by Limit Equilibrium Methods and Finite Element Methods - Irwan, Andesta Granitio; Wiati, Irene Tresna (Departement of Civil Engineering, Faculty of Engineering, 2023)
Slope stability analysis is particularly important for natural slopes that are relatively undesigned to be technically safe. Natural slopes are prone to collapse depending on the condition of the slope material and rainfall. A comprehensive stability analysis using numerical methods to calculate the factor of safety and probability of collapse can be used as a reference to assess the safety of a slope. This study discusses boundary equilibrium and finite element in the analysis of slope safety factor and landslide probability by reconstructing the slope with landslide history. The reconstruction of the slope is based on the actual slope condition with saturated material due to rain that has a safety factor of 0.5 using mathematical methods which are then analyzed numerically in this study. The results of the factor of safety on the saturated condition slope have a value that is not much different from the actual condition with a 100% probability of landslide. The results of low shear strength values in each slice of the limit equilibrium analysis for saturated conditions also indicate that the slope is in an unsafe condition which is supported by the development of shear and tensile strains in the finite element method analysis in the slope slide plane area which causes the stress distribution in the actual landslide area to be unstable.